Edible lies: How Nazi propaganda represented meat to demonise the Jews. (August 2016) - Buscemi, Francesco
This article analyses magazines and books of Nazi propaganda representing meat in order to demonise the Jews. Nazism adopted controversial policies on meat. On the one hand, it banned vegetarian associations; on the other hand, Hitler and many Nazi officials professed their vegetarianism. Moreover, Nazi Animal Protection Law protected animals from the same tortures that the Nazis inflicted in the concentration camps. The article draws on Bauman's theory that Nazism may be understood through the opposition purity/impurity, and on Gambrill's propaganda studies. Moreover, it is based on Elias's Civilising Process and on Fullbrook's 'uncivilising process'. Finally, it focuses on other studies on Nazism and on ancient myths on animals revived by the Nazis. Qualitative propaganda and semiotic analysis focuses on Jews dealing with producing, selling and eating meat. Magazines and books have been sampled according to maximum variation strategy, and therefore this study focuses on a great variety of propagandistic images and texts. Results show that propaganda targeted the Jewish slaughterers, dealers, butchers and eaters in order to represent them as involved in the uncivilising process. In the end, meat contributed to the representation of the Jew as 'impure'. Related to this, blood is overrepresented and is often part of a code of violence that depicts the Jew as separate from the rest of the world, as threatening the German civilising process and, again, as impure. Moreover, the symbolic meat eating contributed to the fabrication of the legend of the Jews as human flesh eaters. Finally, propaganda for children conveyed the Nazi criminal message more directly than any other form.